(untitled) (Jurnal Ekonomi dan Manajemen, 2023)
The era of globalization demands an increase in capacity among public sector employees to achieve optimal work effectiveness. This study analyzes the influence of legal drafting training and the quality of regional legal products on employees’ work ethic and performance at the Regional Secretariat of Mojokerto City. This research uses a quantitative method with an explanatory approach. Data were collected through questionnaires distributed to employees in the institution, and the gathered data were analyzed using statistical methods with SmartPLS. The results indicate that legal drafting training and the quality of legal products significantly affect employees’ work ethic, which in turn improves their job performance. Furthermore, work ethic mediates the relationship between legal drafting training and regulatory quality with employees’ job performance. This finding provides evidence that enhancing competencies in legal drafting and improving the quality of regional legal products have a positive impact on employees’ work behavior. The implications of this research suggest that local governments should optimize training focused on effective regulation drafting and improve the quality of legal products produced. As a result, employees’ performance can be improved, which ultimately contributes to the effectiveness of public policies generated by local governments. This study is expected to provide insights for human resource development policies in the public sector, particularly at the local government level.